Diet composition of a native fish species in a neotropical lentic environment - da Silva, Natália Luiza [UNESP] (2023)
Native species are important to the dynamics of aquatic environments. Studies that seek to understand the basic biology of these species provide information on the species and the dynamics of the natural environment. We characterized the diet, feeding habits, and trophic niche breadth of the native species Hoplosternum littorale (Hancock, 1828) in neotropical lentic environments. Collections were carried out in July 2018 at two sampling points (lagoons) located in the São Francisco Falso River and the Corvo River using gill nets. Stomach content was analyzed, and food items were separated, identified, and quantified using the volumetric method. PERMANOVA analysis was performed to evaluate possible differences in diet between the lagoons. Furthermore, PERMDISP was used to test the trophic niche breadth. Fifteen food items were recorded in the São Francisco lagoon, with the most consumed items being detritus, Diptera (larvae and pupa), and Odonata (nymph). Seven food items were recorded in the Corvo lagoon, with detritus being the most consumed. There was no difference in diet composition and trophic niche breadth between the evaluated lagoons. For both lagoons studied, the species was determined to be a detritivore feeding habit, given its diet's predominant consumption of detritus. The detritivore classification may be related to environmental conditions, food availability, and functional morphology. We also observed the presence of microplastics in the stomachs of some specimens, demonstrating anthropic influence on aquatic environments. Our study contributes to bettering knowledge on this species, and consequently the conservation of the species. It can also serve as a basis for conducting future scientific studies, along with developing the area of study related to Brazilian fish ecology.